USING A USER MODEL FOR ENHANCING ASSESSMENT AND FEEDBACK IN E-LEARNING - Rajibussalim Rajibussalim (Jurnal Natural, 2011)
The study is about a method for enhancing the assessment in e-learning. We study summative assessment that enables teachers or examiners to know if their students have reached an appropriate level of knowledge and formative assessment that enables a student to check how well they are performing in learning. This type of assessment takes the form of a more detailed feedback such as in what aspects a student posses strengths as well as where they have weaknesses. We implement a new approach for enhancing assessment in e-learning by building a system that utilizing a user model to capture user’s knowledge of a concept and to keep updating it in their user models. We implement the system by using the Multiple Choice Questions (MCQs) that were combined with a standard of test called the Question Test of Interoperability (QTI). As the result, more positive and negative feedback can be offered to e-learning users.